Organization of work in the agricultural, forestry, and fishing sector in the US southeast: Implications for immigrant workers' occupational safety and health. Issue 8 (26th March 2013) - Grzywacz, Joseph G.; Lipscomb, Hester J.; Casanova, Vanessa; Neis, Barbara; Fraser, Clermont; Monaghan, Paul; Vallejos, Quirina M.
Abstract Background There is widespread agreement that work organization is an important element of occupational safety and health, but the health effects of many aspects of work organization are likely to vary considerably across different sectors of work and geographies. Methods We examined existing employment policies and work organization‐related research relevant specifically to immigrant workers in the Agriculture, Forestry, and Fishing (AgFF) Sector of the US workforce focusing, when possible, on the southeastern US. Results A number of specific aspects of work organization within AgFF subsectors have been described, but most of this literature exists outside the purview of occupational health. There are few studies that directly examine how attributes of work organization relevant to the AgFF Sector affect workers', much less immigrant workers', occupational health exposures and outcomes. Conclusions In contrast to the broader literature, research linking occupational health outcomes to work organization in the AgFF Sector is limited and weak. A systematic program of research and intervention is needed to develop strategies that eliminate or substantially mitigate the deleterious health effects of occupational exposures whose origins likely lie in the organization of AgFF work. Am. J. Ind. Med. 56:925–939, 2013. © 2013 Wiley Periodicals, Inc.